Case Report: Percutaneous catheter drainage in the treatment of amebic liver abscess with syphilis infections — a case study and literature review - Yang, Ting-Teng; Chuang, Han-Chuan; Chen, Wen-Chao; Hsieh, Yu-Shan (Frontiers in Medicine, 2025)
IntroductionAmebic liver abscesses (ALAs) result from Entamoeba histolytica, a protozoan parasite transmitted through contaminated food or water. Diagnosis relies on imaging and serology, and treatment typically involves antibiotics such as metronidazole.Case presentationHerein, we present a case of a 47-year-old man who presented with hepatitis B virus and syphilis infections during admission. Laboratory tests and computed tomography scan revealed a liver abscess. Percutaneous catheter drainage (PCD) was conducted on the day of admission. Positive amebiasis titers confirmed ALAs. Although culture of the purulent material from the abscess later showed no bacterial growth, ceftriaxone and metronidazole were kept empirically. The patient was discharged in stable clinical condition, and the drainage tube was removed 2 weeks after discharge.ConclusionOur case demonstrated a scenario in which continuous PCD was initiated alongside traditional medical treatment in the risk group for ALAs and PCD complications. The symptoms were successfully relieved, and he recovered well without any complications.